2024
DOI: 10.1177/14713012241249793
|View full text |Cite
|
Sign up to set email alerts
|

Unpaid carers of people with dementia and information communication technology: Use, impact and ideas for the future

Jacqueline Damant,
Paul Freddolino,
Margaret Dangoor
et al.

Abstract: Objectives Several 100,000s of people living with dementia in the UK are cared for at home by a spouse or relative. Few studies have considered the ICT needs and experiences of unpaid carers. This study explores the types of ICT unpaid carers use, the ways they use ICT, the impact of ICT-use, and their ideas for how ICT could be more supportive of their role as a carer. Methods Six focus groups with 32 unpaid carers of people living with dementia discussed their experiences of – and barriers to – using ICT. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Across interviews with nine carers, participants emphasised that digital peer support helped them to maintain their relationship with their cared for person, demonstrate and acknowledge compassion from others, take time to have a personal life and balance this alongside caring, as well as being cognisant of the role they are in and maintaining positivity in it. In a study exploring unpaid dementia carers' experiences of using technology in caring, Damant et al 92 demonstrated carers used social media and videoconferencing or peer support, and daily activities in their personal life, and in supporting them in caring. However, participants emphasised the issues of reliance on technology, and the barriers in terms of access and cost of not only the enabling technology, but in the running costs.…”
Section: Notable Studiesmentioning
confidence: 99%
“…Across interviews with nine carers, participants emphasised that digital peer support helped them to maintain their relationship with their cared for person, demonstrate and acknowledge compassion from others, take time to have a personal life and balance this alongside caring, as well as being cognisant of the role they are in and maintaining positivity in it. In a study exploring unpaid dementia carers' experiences of using technology in caring, Damant et al 92 demonstrated carers used social media and videoconferencing or peer support, and daily activities in their personal life, and in supporting them in caring. However, participants emphasised the issues of reliance on technology, and the barriers in terms of access and cost of not only the enabling technology, but in the running costs.…”
Section: Notable Studiesmentioning
confidence: 99%